Cancer mortality in 1970-1972 among Polish-born migrants to England and Wales. - Adelstein, A. M. (Nature Publishing Group, 1979)
The 1970-72 cancer mortality of Polish migrants to England and Wales is compared with the cancer mortality prevailing in England and Wales and in Poland. Small numbers limit the analyses to the most frequent cancer sites only. The main findings are: (a) Compared with mortality rates in both their country of birth and of adoption, Polish migrants displayed intermediate values for cancers of the stomach, intestinal tract, and lung. For age-groups over 74 years, lung-cancer mortality among the migrants appears, however, to be higher than in both Poland and England and Wales. (b) A distinctly higher mortality among Polish migrants than either in Poland or England and Wales was apparent for lymphomas in both sexes, and for leukaemia and oesophageal cancer in males. (c) Female breast-cancer mortality among Polish migrants was much higher than in Poland, being close to the high mortality rates prevailing in England and Wales. The present findings are compared with the results of similar studies of Polish migrants to the United States and Australia and reasons for observed differences are advanced.